Methods of State Regulation of Informatization Processes in the Republic of Uzbekistan - N.A.Nugmanov; A.U.Kakhramonova (International Journal on Integrated Education, 2022)
In the era of information technologies, specialists at various levels of management are faced with the problems of the competent use of tools for regulating the processes of informatization and the issues of the ways of information development of Uzbekistan are being actively discussed. In this article, we have considered on the concept of "informatization" from a legal, socio-economic point of view. Furthermore, we have identified the main groups of methods used in the state regulation of informatization processes in Uzbekistan.